2012
DOI: 10.1086/664592
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Monitoring of Fecal Cortisol Metabolites in the Eastern Chipmunk (Tamias striatus): Validation and Comparison of Two Enzyme Immunoassays

Abstract: Monitoring fecal glucocorticoid metabolites in wild animals, using enzyme immunoassays, enables the study of endocrinological patterns relevant to ecology and evolution. While some researchers use antibodies against the parent hormone (which is typically absent from fecal samples), others advocate the use of antibodies designed to detect glucocorticoid metabolites. We validated two assays to monitor fecal cortisol metabolites in the eastern chipmunk (Tamias striatus). We compared an antibody produced against c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 53 publications
(86 reference statements)
1
13
0
Order By: Relevance
“…In brief, the assay detects a cortisol response to a standardized ACTH challenge test, as well as circadian variations in fecal cortisol metabolite levels in eastern chipmunks. Our validation also showed that fecal samples collected in this species represent an integrated measure of the cortisol produced over a period of 8 h preceding defecation (Montiglio et al 2012b). We collected fecal samples from the traps during each capture in 2009 (286 samples from 30 females, 9.57 samples/female, range=2-26; 161 samples from 27 males, 5.96 samples/male, range=1-19).…”
Section: Fecal Cortisol Metabolites Collection and Assaymentioning
confidence: 57%
See 3 more Smart Citations
“…In brief, the assay detects a cortisol response to a standardized ACTH challenge test, as well as circadian variations in fecal cortisol metabolite levels in eastern chipmunks. Our validation also showed that fecal samples collected in this species represent an integrated measure of the cortisol produced over a period of 8 h preceding defecation (Montiglio et al 2012b). We collected fecal samples from the traps during each capture in 2009 (286 samples from 30 females, 9.57 samples/female, range=2-26; 161 samples from 27 males, 5.96 samples/male, range=1-19).…”
Section: Fecal Cortisol Metabolites Collection and Assaymentioning
confidence: 57%
“…We previously validated an assay to quantify individual fecal cortisol (see Montiglio et al 2012b for details). In brief, the assay detects a cortisol response to a standardized ACTH challenge test, as well as circadian variations in fecal cortisol metabolite levels in eastern chipmunks.…”
Section: Fecal Cortisol Metabolites Collection and Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Also sex, age, time of the day and even diet may affect the metabolism , Dantzer et al 2011a. Another important matter is the excretion route of the hormone or its metabolites, which can vary significantly between species (Bahr et al 2000, Bamberg et al 2001, Montiglio et al 2012. For some species the main excretion route is feces while some other may excrete the majority of particular hormone metabolites via urine .…”
Section: Introductionmentioning
confidence: 99%